2021
DOI: 10.1186/s12864-021-08095-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the bHLH transcription factor family and its response to abiotic stress in foxtail millet (Setaria italica L.)

Abstract: Background Members of the basic helix-loop-helix (bHLH) transcription factor family perform indispensable functions in various biological processes, such as plant growth, seed maturation, and abiotic stress responses. However, the bHLH family in foxtail millet (Setaria italica), an important food and feed crop, has not been thoroughly studied. Results In this study, 187 bHLH genes of foxtail millet (SibHLHs) were identified and renamed according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 102 publications
3
22
1
Order By: Relevance
“…The clustering of LsbHLHs based on their protein sequence is indicative of functional homogeneity among these genes. This number of bHLH genes is similar to those found in other plant species, such as foxtail millet, where 187 bHLH genes were identified and classified into 21 subfamilies ( Fan et al, 2021) . Tomato also had a high number of bHLH genes, with 159 identified and classified into 21 subfamilies through phylogenetic analysis ( Sun et al, 2015) .…”
Section: Discussionsupporting
confidence: 78%
“…The clustering of LsbHLHs based on their protein sequence is indicative of functional homogeneity among these genes. This number of bHLH genes is similar to those found in other plant species, such as foxtail millet, where 187 bHLH genes were identified and classified into 21 subfamilies ( Fan et al, 2021) . Tomato also had a high number of bHLH genes, with 159 identified and classified into 21 subfamilies through phylogenetic analysis ( Sun et al, 2015) .…”
Section: Discussionsupporting
confidence: 78%
“…All encoded proteins showed signi cant differences; for example, the amino acid length ranged from 94 (BvbHLH62) to 911 (BvbHLH77) amino acids, and the theoretical pI ranged from 4.32 (BvbHLH37) to 11.57 (BvbHLH20) kDa, indicating that the bHLH transcription factor family has diverged inconsistently over the long-term evolution of B. vulgaris, leading to its high complexity [40]. Among them, 80.21% of the BvbHLH proteins had pIs of less than 7, indicating that the B. vulgaris bHLH gene family is rich in acidic amino acids, which is in agreement with ndings related to the bHLH gene family in monocotyledons [35,44,45]. Subcellular localization predictions showed that the vast majority of BvbHLH proteins (90.6%) were localized in the nucleus, suggesting that this family of transcription factors plays a dominant regulatory role, mainly in the nucleus.…”
Section: Identi Cation and Structural Analysis Of The Bvbhlh Genessupporting
confidence: 81%
“…Subcellular localization predictions showed that 87 BvbHLH genes were located in the nucleus, 8 BvbHLH genes were located in the chloroplasts, and BvbHLH16 was located only in the cytoskeleton. The proportion of BvbHLH genes to total genes in the B. vulgaris genome was approximately 0.47%, which was close to Solanum lycopersicum (0.46%) [33], lower than A. thaliana (0.59%) [13], Brachypodium distachyon (0.55%) [16], Fagopyrum tataricum (0.49%) [34], Setaria italica (0.48%) [35], higher than that of O. sativa (0.44%) [16], PopulusL (0.40%) [36], and Hordeum vulgare (0.35%) [37].…”
Section: Characterization Of the Bvbhlh Genementioning
confidence: 99%
“…These proteins play important roles in plants, including controlling flower development [ 2 , 3 ], carbon and nitrogen metabolism [ 4 ], the circadian clock [ 5 ], cell differentiation [ 6 ], hormone response [ 7 ], and disease resistance [ 8 ]. At present, many TFs have been identified and analyzed in foxtail millet, such as NAC [ 9 ], bHLH [ 10 ], AP2/ERF [ 11 ], GRAS [ 12 ], WRKY [ 13 ], and bZIP [ 14 ]. However, few studies have focused on the GATA TF family in foxtail millet.…”
Section: Introductionmentioning
confidence: 99%